Metaverse as developmental ecosystem for students' development - Stchekine, Boris; Sergeyeva, Tetyana; Novytska, Daria (My University, 2023)
It is analyzed the prospect of integrating educational component into the “Metaverse”. It is traced the origin story of the idea from the ancient religious, philosophical and psychological concepts. It is proposed: 1) to create “Metaverse” as developmental ecosystem taking into account the laws of personality development; 2) to involve not only figurative but also abstract thinking to expand the way of describing the “Metaverse” through abstract schemes in addition to images; 3) to introduce moral dimension into the assessment of possible “Metaverse” impact on users’ mind and body as well as on the real world. It is assumed that modeling a digital learning environment based on the internal laws of human development will optimize the entire process. The built-in educational component will provide a virtual learning environment with developmental capacity vastly superior to simulated reality. An innovative Eco-Humanistic Developmental Model is proposed for integration. It is focused on human existential, social and career metasenses of self-development, synergistic interaction and competencies development. In contrast to the situational approach, the process is modeled in its existential integrity. It is based on the idea of human development as a living self-developing system in interaction with the surrounding world as a developmental environment. In the process of balancing actual needs, personal abilities and conditions of environment the synergetic development of all three components is taken place. As a result, not only cognitive and personality development is optimized, but also there is an awareness of interdependence and mutual development of self and environment. The concept, structure, strategy, mechanisms and tools of innovative e-learning courses based on Eco-Humanistic principles are presented. To confirm the efficiency of the proposed approach the results of a research within the framework of a long-term developmental experiment are presented. The prospect of multidisciplinary research is revealed.
Keywords: pedagogical activity; eco-humanistic technology; digitalization; e-learning; modern education